Single nuclear RNA sequencing reveals microglia diversity associated with cognitive resilience in the AD‐BXD mouse model of human Alzheimer's disease: Molecular and cell biology: Inflammatory and microglia‐mediated mechanisms in AD. (7th December 2020) - Heuer, Sarah E.; Zhang, Jigang; Samuels, Michael; Hadad, Niran; Telpoukhovskaia, Maria; Ouellette, Andrew R.; O'Connell, Kristen M.S.; Menon, Vilas; Robson, Paul; Philip, Vivek; Kaczorowski, Catherine C.
Abstract: Background: An individual's genetic background plays an important role in governing the risk (or resilience) to developing Alzheimer's disease (AD) dementia. The goal of this study was to identify the molecular pathways and cell‐types conferring individual differences in cognitive resilience to human familial AD (FAD) mutations that drive high amyloid. Method: A large set of genetically diverse mice harboring familial AD mutations (AD‐BXDs) and their non‐transgenic littermates (Ntg‐BXDs) were tested for short‐ and long‐term memory using contextual fear conditioning at 6m (AD‐BXD n=180, Ntg‐BXD n=174) and 14m (AD‐BXD n=121, Ntg‐BXD n=137). A subset of 14 AD mutation carriers that exhibited extreme resilience (n=7) or susceptibility (n=7) to cognitive decline were selected for hippocampal molecular profiling, along with their Ntg‐BXD littermates, at both 6m and 14m. Data from all hippocampi were aggregated and batch‐corrected using Harmony, and Seurat clustering was employed using the top 2000 variable genes. Known marker genes were used to associate clusters with cell‐types. The fraction of nuclei per sample (cluster composition) and within cell‐type differential gene expression were performed to determine changes in cell quantity and molecular profiles as a function of age, AD mutation carrier status, and resiliency to cognitive decline. Result: There were no clusters that showed significant change in composition as a function of age. However, AD‐BXD individuals had significantly fewer astrocytes and more microglia than their Ntg‐BXD counterparts. We also found that resilient AD‐BXDs had fewer microglia than susceptible individuals, and the number of microglia at 6m was significantly negatively correlated with cognitive decline in AD‐BXD individuals. Additionally, microglia from resilient individuals showed up‐regulation of mitochondrial respiration and protein translation genes, proposing two pathways that dictate resilience in a microglia‐specific manner. Conclusion: Our findings further implicate non‐neuronal cell‐types such as microglia in promoting resilience to cognitive decline in AD, and suggest several pathways by which microglia may be altered in resilient compared to susceptible individuals. We believe that by altering these microglia pathways within susceptible individuals, we can improve how non‐neuronal cells interact with CNS neurons to improve AD cognitive resilience.